Genitorialità migrante: un’esperienza di formazione interculturale con madri immigrate a Napoli - Iavarone, Maria Luisa; Marone, Francesca; Sabatano, Fausta (Rivista Italiana di Educazione Familiare, 2015)
Our contribution is as theoretical and methodological reflection on the specific phenomenon of new immigrant, interfaith families. Some questions were asked about this matter: what happens within these families? Are identity and origin of each parent important predictors of children’s educational models? Which of the two lineages prevails: motherhood or fatherhood? What paths of parenting? Are there differences of gender? These questions will have only partial answers in this reflection; however, our aim is to develop a pedagogical model of the phenomenon, through the description of an educational practice. In terms of education quality, the first question that arises is to bring together these multiplicities and differences within an educational model, whose characteristics of stability, consistency and functionality may help to avoid the risk of confusion and disorientation in subjects who live in real-life complex situations.